Destabilization of Atherosclerotic Plaque by Bilirubin Deficiency. Issue 7 (6th March 2023) - Chen, Weiyu; Tumanov, Sergey; Stanley, Christopher P.; Kong, Stephanie M.Y.; Nadel, James; Vigder, Niv; Newington, Darren L.; Wang, Xiao Suo; Dunn, Louise L.; Stocker, Roland
Abstract : Background: The rupture of atherosclerotic plaque contributes significantly to cardiovascular disease. Plasma concentrations of bilirubin—a byproduct of heme catabolism—inversely associate with risk of cardiovascular disease, although the link between bilirubin and atherosclerosis remains unclear. Methods: To assess the role of bilirubin in atherosclerotic plaque stability, we crossed Bvra −/− with Apoe −/− mice and used the tandem stenosis model of plaque instability. Human coronary arteries were obtained from heart transplant recipients. Analysis of bile pigments, heme metabolism, and proteomics were performed by liquid chromatography tandem mass spectrometry. MPO (myeloperoxidase) activity was determined by in vivo molecular magnetic resonance imaging, liquid chromatography tandem mass spectrometry analysis, and immunohistochemical determination of chlorotyrosine. Systemic oxidative stress was evaluated by plasma concentrations of lipid hydroperoxides and the redox status of circulating Prx2 (peroxiredoxin 2), whereas arterial function was assessed by wire myography. Atherosclerosis and arterial remodeling were quantified by morphometry and plaque stability by fibrous cap thickness, lipid accumulation, infiltration of inflammatory cells, and the presence of intraplaque hemorrhage. Results: Compared with Bvra +/+ Apoe −/− tandem stenosis littermates, Bvra −/− Apoe −/− tandem stenosis mice were deficient in bilirubin, showed signs of increased systemic oxidative stress, endothelial dysfunction, as well as hyperlipidemia, and had a higher atherosclerotic plaque burden. Heme metabolism was increased in unstable compared with stable plaque of both Bvra +/+ Apoe −/− and Bvra −/− Apoe −/− tandem stenosis mice and in human coronary plaques. In mice, Bvra deletion selectively destabilized unstable plaque, characterized by positive arterial remodeling and increased cap thinning, intraplaque hemorrhage, infiltration of neutrophils, and MPO activity. Proteomic analysis confirmed Bvra deletion enhanced extracellular matrix degradation, recruitment and activation of neutrophils, and associated oxidative stress in unstable plaque. Conclusions: Bilirubin deficiency, resulting from global Bvra deletion, generates a proatherogenic phenotype and selectively enhances neutrophil-mediated inflammation and destabilization of unstable plaque, thereby providing a link between bilirubin and cardiovascular disease risk.